BIMBINGAN DAN PELATIHAN ASPEK LEGALITAS USAHA DAN PERPAJAKAN PADA USAHA JASA BOGA DI KECAMATAN LOWOKWARU KOTA MALANG - Novi Nugrahani; Galuh Kartiko; Atik Andhayani; Siti Amerieska; Putri Ayu B (Pusat Riset dan Inovasi Nasional, 2022)
ABSTRACT A business requires business legality as evidence of ratification of a business entity. Legality must be proven by valid documents according to applicable laws and regulations so that businesses are protected. In addition to business legality, catering services must also carry out tax obligations. Catering services are one of the objects of income tax (PPh). If the catering business takes the form of a corporate body, income tax art 23 will be collected and income tax art 21 will be collected if it is an individual business (as a non-employee receiving unsustainable income). This Community Service Activity is expected to provide knowledge about business legality and taxation aspects, especially with the enactment of the Job Creation Act and the Law on Tax Regulations Harmonization. Keywords: income tax art 21, income tax art 23, catering